ANALISIS KEPUASAN KERJA, LINGKUNGAN KERJA, WORK-LIFE BALANCE DAN BUDAYA KERJA TERHADAP LOYALITAS PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN LABUHANBATU - Sinaga Simanjorang, Elida Florentina (Universitas Labuhanbatu, 2021)
Employees are an important resource for almost any organization because employees are an investment and a source of competitive advantage for businesses and agencies. Retaining competent employees and developing employee loyalty is increasingly important and are a constant challenge. This study aims to determine the analysis of job satisfaction, work environment, work-life balance, and work culture on employee loyalty at the Regional Disaster Management Agency (BPBD) Labuhanbatu Regency. The data analysis technique in this study is multiple linear regression analysis. Based on the results of partial analysis, it is found that job satisfaction has a positive and significant effect on employee loyalty, the work environment has a positive and significant effect on employee loyalty, work-life balance has a positive and significant effect on employee loyalty and work culture also has a positive and significant effect on employee loyalty. Based on the simultaneous test results, the four variables also have a positive and significant effect.